2015
DOI: 10.1245/s10434-015-4759-x
|View full text |Cite
|
Sign up to set email alerts
|

Toolbox to Reduce Lumpectomy Reoperations and Improve Cosmetic Outcome in Breast Cancer Patients: The American Society of Breast Surgeons Consensus Conference

Abstract: BackgroundMultiple recent reports have documented significant variability of reoperation rates after initial lumpectomy for breast cancer. To address this issue, a multidisciplinary consensus conference was convened during the American Society of Breast Surgeons 2015 annual meeting.MethodsThe conference mission statement was to “reduce the national reoperation rate in patients undergoing breast conserving surgery for cancer, without increasing mastectomy rates or adversely affecting cosmetic outcome, thereby i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 119 publications
2
85
0
4
Order By: Relevance
“…Recent efforts to standardize the approach to addressing pathologic margin status also have the potential to effect reoperation rates 45 . Although no clear single solution has emerged, high variability suggests this intervention could be a useful quality measure 7,11,12 , or at least a factor that affects patient satisfaction and cost 46,47 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent efforts to standardize the approach to addressing pathologic margin status also have the potential to effect reoperation rates 45 . Although no clear single solution has emerged, high variability suggests this intervention could be a useful quality measure 7,11,12 , or at least a factor that affects patient satisfaction and cost 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Although no consensus on the optimal reoperation rate has been reached, several international bodies have, as noted earlier, suggested that reducing the number of repeat operations is a necessity [7][8][9] , with one organization suggesting 10% as a goal 9 . A number of institutional publications have reported reoperation rates close to that benchmark 1,8,34 , suggesting that it is achievable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of local treatment depends on having clear resection margins. Residual cancer in resection margins can be found in as many as 20-46% of patients treated by BCT [2][3][4] which significantly increases the risk of recurrence, with ductal carcinoma in situ (DCIS) being particularly difficult to excise [5]. It is therefore vital to evaluate the clearance of excision margins.…”
Section: Introductionmentioning
confidence: 99%